Controlling the Behavior of Cancer Cells Using Electro magnetic Fields in the Orchestrated Objective Reduction Model (Global Journal of Sciences, 2025)
In this paper, we propose a novel theoretical framework within the orchestrated objective reduction (Orch OR) model to investigate the role of electromagnetic fields in controlling the behavior of cancer cells. According to our approach, the brain captures, stores, and analyzes cellular information through electromagnetic signaling, subsequently sending regulatory commands to maintain normal cellular function. When cells undergo malignant transformation, the stored information and the corresponding electromagnetic signals change, providing an opportunity for early detection of tumor formation. We further suggest that by storing the correct information and transmitting appropriate electromagnetic signals, the brain may create the conditions necessary to restore cancerous cells to their normal state. This work introduces a new perspective on the early diagnosis and potential control of cancer based on quantum neurobiological principles.
Keywords: Orch OR Model; Cancer; Quantum Information; Electromagnetic Waves